THE IMPLEMENTATION OF E-GOVERNMENT IMPLEMENTATION POLICY IN SAYANG VILLAGE, SUMEDANG DISTRICT - Indra Gunawan Wibiksana; Desti Lestary; Ahmad Ulul Azmi; Dicky Setiawan Nugroho; Hayatul Insan (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2019)
Implementation of e-Government in the village dear by referring to presidential instruction number 3 Implementation of e-Government Policy in Quality Improvement is still at the stage of preparing access facilities such as a limited wifi connection, as well as a lack of socialization of information sites to the public. The research method used by researchers is a qualitative research method with a desktiptif approach. Data collection techniques are carried out by means of literature studies and field studies. As for the indicators of basic values in determining the success and failure of applications that will and must be achieved in implementing e-Government there are 4 namely effectiveness, efficiency, transparency and accountability. The application of e-Government policies in Sayang Village is still not optimal in the use of communication and information technology. The Village Government unfortunately has not been effective, efficient, transparent and accountable in implementing E-Government-based governance.